2020
DOI: 10.2147/cmar.s227327
|View full text |Cite
|
Sign up to set email alerts
|

<p>The lncRNA BCYRN1 Functions as an Oncogene in Human Glioma by Downregulating miR-125a-5p in vitro</p>

Abstract: Introduction: Numerous studies have demonstrated that long noncoding RNAs (lncRNAs) are deregulated in many cancers and exert their functions through multiple cancer-related biological processes. Glioma is the most common primary malignant central nervous system tumor and has a high fatality rate in adults. In current study, we aimed to determine the role and functional mechanism of the lncRNA BCYRN1 in glioma. Methods: Gain-of-function and loss-of function approaches were used to investigate the function of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Bioinformatics and luciferase reporter assays revealed that LINC00174 may competitively bind to miR‐1910‐3p to increase TAZ expression in CRC carcinogenesis 32 . MiR‐125a‐5p, an important endogenous tumour suppressor, 40 was reported to target TAZ and inhibit EGFR pathway to repress retinoblastoma progression 41 . A recent study performed by Yu et al 40 suggested lncRNA BCYRN1 functioned as an oncogene by sponging miR‐125a‐5p to activate TAZ, and then results in cell proliferation, invasion and migration in glioma.…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%
“…Bioinformatics and luciferase reporter assays revealed that LINC00174 may competitively bind to miR‐1910‐3p to increase TAZ expression in CRC carcinogenesis 32 . MiR‐125a‐5p, an important endogenous tumour suppressor, 40 was reported to target TAZ and inhibit EGFR pathway to repress retinoblastoma progression 41 . A recent study performed by Yu et al 40 suggested lncRNA BCYRN1 functioned as an oncogene by sponging miR‐125a‐5p to activate TAZ, and then results in cell proliferation, invasion and migration in glioma.…”
Section: Regulatory Network Of Lncrnas and Hippo Signalling Pathway Imentioning
confidence: 99%
“…BCYRN1, termed as BC200, has been found in a variety of cancers as previous studies. Either as an oncogenic lncRNA or a tumor suppressor, BCYRN1 was reported to exert significant biological function in cancers such as NSCLC, ovarian cancer, and gastric cancer [31,[44][45][46][47][48]. However, as a lncRNA derived from brain cytoplasm, the expression and function of BCYRN1 in glioma remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…BCYRN1 is a newly identified lncRNA with similar characteristics [ 15 ]. Previous studies have revealed that miRNAs, such as miR-125-5p, miR-149 and miR-490-3p, act as targets of BCYRN1 in hepatocellular carcinoma, human glioma and lung cancer, respectively [ 17 , 40 , 41 ]. Recently, the relationship between BCYRN1 and CRC has been gradually observed.…”
Section: Discussionmentioning
confidence: 99%